Reliability and validity of the Upper Limb Functional Test (ULIFT) for women after breast cancer surgery - Prim A.C.* (2022)
© 2021 Informa UK Limited, trading as Taylor & Francis Group.Purpose: To evaluate the reliability and convergent validity of the Upper Limb Functional Test (ULIFT) in women after breast cancer surgery. Materials and methods: A cross-sectional study with 25 women (mean age 50 ± 7.3 years) with breast cancer submitted to a surgery intervention within a minimum period of three years. Intraclass correlation coefficients (ICCs) were calculated to assess the test–retest reliability. A Bland–Altman plot examined the agreement between the times to complete two tests. Validity was established by correlating the ULIFT and DASH total score. The receiver operating characteristic (ROC) curve was used to determine the cut-off point for ULIFT in order to discriminate patients with some level of upper limb dysfunction. Results: The ULIFT showed high reproducibility (ICC = 0.89; p < 0.001), learning effect of 7.21%, and a moderate correlation with the DASH total score (r = 0.536; R 2 = 0.28; p = 0.006). The standard error of measurement was 6.9 s and the smallest real difference was 19.1 s. The ROC curve indicated a cut-off point of 109.2 s (sensitivity = 68.7%; specificity = 77.8%; area under ROC curve = 0.77). Conclusions: The ULIFT could be a valid and reliable test to assess upper limb functionality in patients submitted to breast cancer surgery.Implications for rehabilitation The ULIFT is a reliable and valid test to assess upper limb function in women after breast cancer surgery, considering specifically the lifting and range of motion construct of unilateral upper limb function. The ULIFT could help identify those most at risk of developing upper limb dysfunction after breast cancer surgery and could benefit the follow-up of a postoperative rehabilitation program. Two ULIFTs should be performed in order to achieve patient’s best performance.